Galvanic plating for 3D-MID applications - Kordaß, Timo; Franke, Jörg (Proceedings of the 2014 37th International Spring Seminar on Electronics Technology, ISSE 2014, 2014)
This paper gives an overview about the advantage of galvanic plating for 3D-MIDs. At first it is explained how the laser direct structuring process is proceeded. Exemplary on a serial application for motorcycles it shows the challenges for the chemical standard plating in the serial processes in the first part. The second part illustrates the differences in the plating processes between the galvanic and the chemical precipitation. The advantages with major coating thickness for further developed applications are mentioned. It is also given the particular specifics need to be considered in the development for the galvanic process.
CRIS-Team Scopus Importer:2023-03-07